2016
DOI: 10.3109/08820139.2016.1153650
|View full text |Cite
|
Sign up to set email alerts
|

Association ofInterleukin-1BandInterleukin-4Gene Variants with Autoimmune Thyroid Diseases in Tunisian Population

Abstract: Autoimmune thyroid diseases (AITD) including Graves' disease (GD) and Hashimoto's thyroiditis (HT) are complex genetic diseases. Cytokines IL-1B and IL-4 play a role in the pathogenesis of AITD. This study was conducted on Tunisian patients with GD or HT to investigate the association of IL-1B and IL-4 gene polymorphisms with the risk and the prognosis of AITD. A total of 358 healthy controls and 341 patients with AITDs (249 HT and 92 GD) were genotyped for IL-1B+3953C/T and IL-4 intron 3 VNTR polymorphisms. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
1
12
0
4
Order By: Relevance
“…The pro-inflammatory effect of IL-1β is based on bone resorption by activation of osteoclasts and encouraged RANKL expression. 35,36 This study showed a statistically significant positive linear relationship between age, anti-dsDNA, anti-CCP, RF and duration of thyroiditis with the occurrence of rheumatic diseases, with anti-dsDNA and RF being the most significant predictors. A recent study on hypothyroid/euthyroid postmenopausal women disclosed that TSH positively correlated with OPG and negatively with IL-6 and osteocalcin, moreover that thyroid autoimmunity can affect OPG/RANKL levels independently of hypothyroidism.…”
Section: Discussionmentioning
confidence: 55%
“…The pro-inflammatory effect of IL-1β is based on bone resorption by activation of osteoclasts and encouraged RANKL expression. 35,36 This study showed a statistically significant positive linear relationship between age, anti-dsDNA, anti-CCP, RF and duration of thyroiditis with the occurrence of rheumatic diseases, with anti-dsDNA and RF being the most significant predictors. A recent study on hypothyroid/euthyroid postmenopausal women disclosed that TSH positively correlated with OPG and negatively with IL-6 and osteocalcin, moreover that thyroid autoimmunity can affect OPG/RANKL levels independently of hypothyroidism.…”
Section: Discussionmentioning
confidence: 55%
“…IL‐1β is a protein known by its crucial pathophysiological role in inflammatory disorders and its influence in silicosis susceptibility and/or severity has been investigated in several animal model studies, and in a clinical study . We hypothesized that there is a possible association of the IL1B +3954C>T polymorphism with the severity of silicosis, since this polymorphism has been previously associated with the severity and susceptibility to several inflammatory diseases . However, no association of the IL1B +3954C>T polymorphism with silicosis severity was detected (simple or complicated silicosis) in the present work.…”
Section: Discussionmentioning
confidence: 97%
“…Buccal cell samples were obtained by mouthwash with 5 mL of saline solution for 60 seconds, identified, and immediately stored in a freezer at −4°C. The genomic DNA extraction was performed directly from saliva by the method described by AIDAR and LINE …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we showed also the implication of IL‐4 polymorphism in HT. We found an association between a variable number of tandem repeat (VNTR) polymorphism in intron 3 of the IL‐4 gene and HT susceptibility (Zaaber et al, ). Our results are in line with the study of Hunt and collaborators who showed an association between IL‐4 rs2243250 polymorphism and HT (Hunt et al, ).…”
Section: Discussionmentioning
confidence: 99%